Propaganda Putih Kampanye Moderasi Beragama Menggunakan Hashtag di Media Sosial X - Arif Budiwinarto; Mochamad Syaefudin (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The advancement of information technology has significantly transformed how people communicate and share information, including within religious contexts. Social media platforms, particularly Twitter/X, have emerged as strategic channels for disseminating religious messages one of which is through the use of hashtags (#), which enable categorization and wider dissemination of content. Amid Indonesia's diverse society, religious moderation has become an urgent need to mitigate potential interfaith conflicts. This study aims to examine how "white propaganda" is utilized in digital campaigns promoting the principles of religious moderation by government institutions and religious organizations. Employing a descriptive qualitative approach, this research collects data through documentation and literature review. The findings are expected to illustrate forms of digital communication strategies—specifically white propaganda—that effectively disseminate the values of tolerance, balance, and justice in religious practice. Furthermore, the study contributes to the development of communication science, particularly in the domains of digital communication and religious social campaigns.